Morphogenesis in tissue culture of kazakh cotton varieties (Experimental biology, 2015)
Its presented the dependence of callus formation process on the type, size and composition of the explant culture medium. The optimal culture media are revealed for callus formation and somatic embryogenesis in cotton.
Keywords: callus tissue; somatic embryogenesis; morphogenesis of cotton